PERAN PENYIDIK KEPOLISIAN TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM DALAM PERSPEKTIF RESTORATIVE JUSTICE - Imam Muhdi (Universitas Borneo Tarakan, 2020)
Abstract Children are the hope of the nation. But reality shows that children are still involved in various forms of crime. Meanwhile, the police as law enforcers are expected to handle criminal cases involving children as a perpetrator with a different approach, namely the approach of restroative justice. This is what becomes the rationale for research with two objectives: (1). The role of police investigators on children in conflict with the law with a restroative approachjustice; (2). Forced efforts that can be carried out by police investigators on children in conflict with the law. This research is a normative study with two approaches, namelylegislation approach and conceptual approach. Based on this approach, the overall results of the study were analyzed argumentatively qualitatively. The results of the study indicate that police investigators have a very important roleimportant in handling crime cases involving children by exposing the child to putting forward the approach of restroative justice. The results of subsequent research, that forced efforts by police investigators againstchildren who are in conflict with the law in the approach of restroative justice, which should prioritize human values by integrating the role of the community, given the development of the child's soul. The recommendation of researchers is that police investigators handling child crimes should be provided with special skills that prioritize the approachrestroative justice. Keywords: Children, Police Investigators, and Restorative Justice